Dynamical opacity-sampling models of Mira variables - II. Time-dependent atmospheric structure and observable properties of four M-type model series - Ireland, Michael J.; Scholz, Michael; Wood, Peter R. (Monthly notices of the Royal Astronomical Society, 2011)
We present four model series of the CODEX dynamical opacity-sampling models of Mira variables with solar abundances, designed to have parameters similar to o Cet, R Leo and R Cas. We demonstrate that the CODEX models provide a clear physical basis for the molecular shell scenario used to explain interferometric observations of Mira variables. We show that these models generally provide a good match to photometry and interferometry at wavelengths between the near-infrared and the radio, and make the model outputs publicly available. These models also demonstrate that, in order to match visible and infrared observations, the Fe-poor silicate grains that form within 3 continuum radii must have small grain radii and therefore cannot drive the winds from O-rich Mira variables.